(untitled) (Sebha University Conference Proceedings, 2024)
This study addresses an urban problem that negatively affects the urban environment of cities, It is neglecting the squares and open areas in residential complexes, as these squares and open areas are considered the lungs of cities in general and residential areas in particular. It is an element of sustainability. Which plays a major role in the sustainable urban design process and contributes to meeting the needs of the residents of these communities and providing all their services. Hence the importance of this study, which highlights the importance of open areas and their role in achieving a sustainable urban environment and what they reflect on the city on the other hand. This study aims to identify the concepts of sustainable urban environment and how to achieve them in the study area and their impact on humans from all social and cultural aspects. The researchers in this study relied on the descriptive and analytical approaches for the Al Hilal Buildings area in the city of Tarhuna to reach results that could give the required importance to open areas and identify the factors that contribute to achieving a sustainable urban environment.